Gender differences of health literacy in persons with a migration background: a systematic review and meta-analysis - Elke Kalbe; Nicole Skoetz; Christiane Woopen; Digo Chakraverty; Annika Baumeister; Angela Aldin; Ümran Sema Seven; Ina Monsef (BMJ Open)
Objective To investigate gender differences of health literacy in individuals with a migration background.Design Systematic review and meta-analysis. OVID/MEDLINE, PsycINFO and CINAHL were searched in March 2018 and July 2020.Setting Studies had to provide health literacy data for adult women and men with a migration background, collected with a standardised instrument, or report results that demonstrated the collection of such data. Health literacy data were extracted from eligible studies or requested from the respective authors. Using a random-effects model, a meta-analysis was conducted to assess standardised mean differences (SMDs) of health literacy in men and women. Two researchers independently assessed risk of bias for each included study using the Appraisal Tool for Cross-Sectional Studies.Results Twenty-four studies were included in this systematic review. Thereof, 22 studies (8012 female and 5380 male participants) were included in the meta-analyses. In six studies, gender-specific health literacy scores were reported. The authors of additional 15 studies provided their data upon request and for one further study data were available online. Women achieved higher health literacy scores than men: SMD=0.08, 95% CI 0.002 to 0.159, p=0.04, I2=65%. Another 27 studies reported data on female participants only and could not be included due to a lack of comparable studies with male participants only. Authors of 56 other eligible studies were asked for data, but without success.Conclusion Men with a migration background—while being much less frequently examined—may have lower health literacy than women. As heterogeneity between studies was high and the difference became statistically insignificant when excluding studies with a high risk of bias, this result must be interpreted with caution. There is a paucity of research on the social and relational aspects of gender in relation to health literacy among people with a migration background, especially for men.PROSPERO registration number CRD42018085555.